2015
DOI: 10.1134/s0026261715010154
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in metabolism of purple bacteria and prospects of practical application

Abstract: Purple bacteria are able to use H 2 for photoautotrophic, photomixotrophic, and chemoau totrophic growth, exhibiting high metabolic lability. Depending on the type of metabolism, hydrogen may be consumed with release of energy and/or reductive equivalents. Purple bacteria may also release H 2 as a ter minal electron acceptor or in the course of dinitrogen fixation. Thus, hydrogen metabolism in purple bacteria is diverse; these bacteria are often used as models for investigation of the metabolic traits and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…Taking into account the fact that that this hydrogenase is stable and can work even at 70°C, one can conclude that it is a very promising enzyme for use in enzymatic hydrogenase electrodes. Several schemes of HydSL hydrogenase participation in metabolism of T. bogorovii BBS exist [ 14 , 66 , 73 ]. All of them indicate that HydSL hydrogenase in purple bacteria is closely connected with sulfur metabolism but, unfortunately, none of them took into account all valid experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the fact that that this hydrogenase is stable and can work even at 70°C, one can conclude that it is a very promising enzyme for use in enzymatic hydrogenase electrodes. Several schemes of HydSL hydrogenase participation in metabolism of T. bogorovii BBS exist [ 14 , 66 , 73 ]. All of them indicate that HydSL hydrogenase in purple bacteria is closely connected with sulfur metabolism but, unfortunately, none of them took into account all valid experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme can be arranged into four categories. The Group I H 2 ‐consuming membrane‐bound hupSL hydrogenase is found in both aerobic and anaerobic bacteria ( Aquefixaeolicus ) with an electron transport system via cytochromes 1, 101. This enzyme structure is recognized by a signal peptide linked at the N ‐terminus of a small subunit 29, 101.…”
Section: Enzymes Involved In Biohydrogen Productionmentioning
confidence: 99%
“…were identified. Later, studies demonstrated the presence of hydrogenase enzymes in these species as biohydrogen consumers to control their redox cellular status 1, 101. The enzyme structure consists of two metal irons including sulfur bridges [Fe‐S] in the active site while linked to CO and CN − groups (Fig.…”
Section: Enzymes Involved In Biohydrogen Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photobiological production of hydrogen (H 2 ) is considered to be one of the most promising technologies for replacing or complementing fossil fuel-derived energy. In contrast with electricity generated by solar panels and wind mills, H 2 is more easily stored and transported from overseas [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%